Entrance to the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance to the Kaner-ki-Putli Temple is through the antarala (vestibule or antechamber), which has two square-shaped pilasters. These pilasters feature carvings of dvarapalas (door guardians) at the base, with decorative ornamentation on the upper portion.